A comparative evaluation of the South African income tax regime for investments using trusts - Herbst, Hendri (Stellenbosch University, 2023)
This study evaluates the South African income tax regime for investments using trusts. It considers whether reforms are required, and if so, how can this be done to create a tax framework that will encourage investment, limit tax avoidance and curb capital outflows, while considering South Africa’s unique context and challenges.
Keywords: Income tax; Investments; Taxation; Trusts and trustees

Legal protection of the individual's image against unauthorised commercial exploitation in South Africa : a critical evaluation of existing law and suggestions for law reform - Van Gensen, Layckan Inge (Stellenbosch University, 2023)
Keywords: Commercial exploitation; Human rights; Image rights; Intangible property; Intellectual property; Personality; Right of privacy

Developing a legal framework for determining forum choices in transnational intellectual property litigation - Ho, Vannessa May Ha (Macquarie University, 2023)
As communication technologies have assisted in the rapid transfer of information and goods across borders, there has been a commensurate rise in transnational intellectual property litigation. In particular, use of the Internet for trade and consumption of information has led to simultaneous infringement of parallel intellectual property rights in multiple States. The chosen forum to resolve such a dispute is perceived to have significant effect upon the outcome of litigation. There is a need to closely evaluate current jurisdiction rules and recent reform proposals to determine the extent to which they facilitate or prevent litigants from making forum choices that can promote efficiency and fairness in the dispute resolution process. However, there is currently no formal international treaty that regulates how litigants may make forum choices during transnational intellectual property litigation. As a result, the range of forum choices available to litigants are determined by divergent domestic rules, meaning that litigants must enforce their intellectual property rights in forums within every State where the rights exist and have been infringed upon. In such as context, a critical issue is to consider is whether an international regulatory framework could be developed to facilitate appropriate forum choices which advances and calibrates efficiency and fairness in transnational intellectual property litigation. As most conceptions of appropriate forums are from a doctrinal perspective, it is necessary to create a theoretical framework to determine what constitutes an appropriate forum choice during a transnational intellectual property dispute. This theoretical framework can then be used to evaluate the merits of current rules on jurisdiction and determine whether they define a suitable range of available forums that allow litigants to make appropriate choices. The forum non conveniens doctrine also needs to be evaluated as it has the most developed case law that considers appropriate forums for civil disputes. Finally, the risks and benefits of developing an international regulatory framework needs to be examined to assess which method would be the most suitable way to facilitate appropriate forum choices. It is hoped that this research will assist courts and legal practitioners when making decisions about complicated jurisdiction issues during transnational intellectual property disputes, as well as enable policy makers to promote reform that facilitates more efficient and fair forum choices.
Keywords: Forum choice; Forum non conveniens; Forum shopping; Intellectual property litigation; International regulatory framework; Kyoto Guidelines; Lucasfilm v Ainsworth; Private international law; Rational choice; Subject matter jurisdiction

Party autonomy and judicial participation in commercial arbitration: recalibrating the role of Nigerian courts. - Aduloju, Bamikole Martins (Robert Gordon University, 2023)
Courts and arbitration tribunals aim to resolve disputes and make enforceable decisions in their distinctive way. However, unlike courts, tribunals lack state enforcement power to function independently. Consequently, arbitrating parties have had to approach the courts for various supports. However, while supporting arbitration, the Nigerian courts have been criticised for overwhelmingly undermining party autonomy. Thus, the determination of the extent to which Nigerian courts should participate in arbitration remains topical. This research reviewed the current regime governing the scope and limits to the court's roles in arbitration in Nigeria, aiming to find out the problematic areas where the court's roles have been a leeway to undermine party autonomy. The research found that the current practice in Nigeria generally observes party autonomy as an affirmative stance by the Nigerian courts and laws. It further found the areas where the Nigerian system has, nevertheless, created some leeway for the courts to undermine party autonomy. These include (i) the narrow phrasing and interpretation of Section 34 of the Act and some specific provisions, and their failure to set out a definite limit to courts' roles in arbitration, (ii) the application of the concept of constitutional supremacy which has been interpreted to allow Nigerian courts to participate in all cases including arbitration and override parties' agreement, (iii) absence of Institutionalised tracking and periodic recalibration of the relationship between the courts and arbitration, and (iv) judicialisation of administrative roles of the courts in arbitration. To this end, a legal and analytical review of these problematic issues was conducted, particularly using some elements of the legal comparative approach to analyse the problems in the light of the related practices in some similar or advanced jurisdictions such as the United Kingdom, Ghana and Malaysia. Lessons were drawn from the analysis. Short- and long-term recommendations were, therefore, made for law reforms in Nigeria, particularly towards recalibrating the court's roles in arbitration such as to wedge the loopholes in the system without which recalcitrant parties and jurists could take advantage to undermine party autonomy.
Keywords: Arbitrage; Arbitragem; Arbitration; Autonomy; Court systems; Judiciary; Tribunals

Prospects for an African continental model multilateral tax agreement for the co-ordination of cross-border corporate tax challenges - Fehun Aren, Marie-Louise (University of Pretoria, 2023)
This study explores the creation of an African Continental Model Multilateral Tax Agreement (MMTA) to address the limitations of current bilateral tax treaties and enhance existing African Regional Economic Community (REC) frameworks for more effective taxation of cross-border business profits. Focusing on critical international taxation framework issues such as taxing rights allocation, Permanent Establishment criteria, and tax dispute resolution, it compares African REC MMTA provisions with those in non-African agreements to identify key weaknesses and propose improvements. The proposed MMTA aims to ensure equitable taxing rights, update nexus rules to capture both physical and digital businesses, and provide robust dispute resolution mechanisms to foster investment. It advocates for harmonized tax policies and tax agreements across African RECs to minimize tax competition, promote intra-African trade, and support regional economic integration under the African Continental Free Trade Area (AfCFTA). By aligning with the Abuja Treaty’s objectives, the framework seeks to enhance revenue mobilization and sustainable economic development in Africa. This research provides a roadmap for creating a tailored multilateral tax treaty that balances diverse regional interests, addressing Africa’s development financing needs while promoting cross-border taxation efficiency.
Keywords: AfCFTA; African Continental Free Trade Area; Continental model; International taxation frameworks; Multilateral tax agreement; Revenue mobilisation; Tax treaties

An analysis of merger and amalgamation transactions under the Companies Act 71 of 2008 and the Income Tax Act 58 of 1962 - Meyer, Carolina (University of Pretoria, 2023)
In law it is common to encounter two separate pieces of legislation which govern a single matter or transaction, for example, the Companies Act 71 of 2008 (the Companies Act) and the Securities Transfer Act 25 of 2007 both of which address the sale of shares. Similarly, the Income Tax Act 58 of 1962 (the Income Tax Act) and the Companies Act both have regulations which govern, respectively, tax law and company law matters in South Africa. These two Acts overlap in various business and commercial fields as tax is frequently an important component of any business transaction undertaken by a company. Issues, however, arise when the regulations in these two Acts, are inconsistent. This can be observed if one compares the current South African Income Tax and Companies Act, specifically as regards the sections involving merger and amalgamation transactions. Section 44 of the Income Tax Act governs merger and amalgamation transactions from a tax perspective and provides for tax rollover relief if certain requirements are met. The regulations governing mergers and amalgamations under the Companies Act are contained in sections 113, 115 and 116 of the Act. Although these sections in both Acts address the same transaction – a merger or amalgamation between two or more companies – there are several discrepancies between the regulations in the two Acts which appear to operate entirely independently of one another. In practice, one often sees that other sections in the Companies Act and Income Tax Act are used to achieve a merger due, in the main, to the uncertainties in the application of the relevant merger sections in the two Acts and the limited interaction between them. This study identifies and assesses the impact of the discrepancies identified in these two Acts in relation to merger and amalgamation transactions. The study makes recommendations to address these discrepancies and to align the South African Companies Act and Income Tax Act as regards merger/amalgamation transactions.
Keywords: Amalgamation; Companies Act; Income Tax Act; Merger; Taxation

Earnings Management and Default Risk - Nguyen, Loan (Victoria University of Wellington, 2023)
This thesis comprehensively investigates the relationship between default risk (DR) and earnings management (EM) by addressing inconsistencies in prior research regarding the level and direction of EM in response to varying levels of DR. The thesis extends beyond severe financial distress to include firms with low and medium levels of distress. It examines the non-monotonic relationship between DR and EM, considering accrual earnings management (AEM), real earnings management (REM), and total earnings management (TEM). The thesis also examines the impact of DR on the relative use of REM versus AEM. The moderating effect of the global financial crisis (GFC) on the relationship between DR and EM is also explored.Using a sample of 29,228 firm-year observations from 4,514 US-listed firms during 2001-2019, the study employs both the traditional two-step and the more recent one-step approaches to identify EM. Sensitivity analysis is conducted, including and excluding mining firms.The findings reveal a non-monotonic relationship between DR and REM, with a concave pattern observed for all measures of REM. Initially, REM increases as DR rises, but it subsequently declines with further increases in DR. AEM, on the other hand, shows a convex or monotonically decreasing relationship with DR, although statistical significance is not consistently observed. The results for TEM align with those of REM, indicating the dominance of REM in TEM. These findings remain consistent when excluding mining industry observations and using different measures for EM and DR.The implications of these findings are significant for managers, firms, regulators, lenders, investors, and other stakeholders. The non-monotonic relationship between DR and REM offers insights for decision-making and determining appropriate levels of EM during varying levels of DR. Regulators can utilise this relationship to identify potential risk areas and develop effective regulations. Lenders can assess financial statements more vigilantly, and investors can make more accurate risk assessments and informed investment decisions. The robustness of the results and the inclusion of different EM measures provide valuable insights to auditors, analysts, and government professionals, enhancing their understanding of the complexities and risks associated with EM during varying levels of DR.The study also uncovers that the relative use of AEM and REM is complimentary, but the impact of DR dampens the increase in REM for a given increase in AEM. This result holds across primary and alternative measures of DR and is of significant interest to managers, firms, regulators, and other stakeholders. It provides insights into the interplay between AEM and REM, enabling informed decisions about EM strategies under different levels of DR. Regulators can leverage this information to identify potential risk areas and develop effective regulations to mitigate EM practices that could lead to financial instability. Lenders and investors benefit from understanding how DR affects the relative use of AEM and REM, enabling them to assess financial statements and manage investment risk more accurately. The study’s findings contribute to a deeper understanding of EM dynamics and have practical implications for various stakeholders in the financial ecosystem.Furthermore, the thesis investigates EM measures during the GFC and the moderating effect of the GFC on the relationship between DR and EM. The inclusion of REM and TEM, in addition to AEM, provides a comprehensive understanding of how firms managed their earnings during the GFC, offering insights into the effectiveness and implications of different EM strategies during a financial crisis. It confirms the decline of AEM during the GFC, reinforcing existing knowledge about the impact of the crisis on EM practices. Additionally, it identifies a negative impact of the GFC on REM and TEM, providing further evidence of the challenges and changes in EM strategies faced by firms during the economic crisis. The study also finds an insignificant moderating effect of the GFC on the relationship between DR and REM, as well as DR and TEM, shedding light on EM variation across different economic stages.Overall, this thesis contributes to the EM literature by examining the non-monotonic impact of DR on EM measures, comparing different approaches to identify EM, exploring the moderating effect of DR on the relative use of AEM and REM, and investigating EM measures during the GFC. The insights from this research assist managers in decision-making, firms in adapting financial management strategies, regulators in developing policies, lenders in risk assessment, and investors in understanding the complexities and risks associated with EM. The findings have practical implications for various stakeholders in the financial realm, guiding decision-making, regulatory efforts, risk assessment, and investment strategies.Keywords: earnings management, accruals earnings management, real earnings management, default risk, global financial crisis, one-step approach, two-step approach.

The Law of the Sea and Nigeria's Marine Policy: A Critical Evaluation - Tagowa, Wonotanzokan Nzeda (Ahmadu Bello University, 2023)
Keywords: Droit maritime; Marine policy; Nigeria; Sea

Fishing for Rights ! The Protection of the Individual in Fisheries - Longo, Andrea (Università degli studi di Milano, 2023)
La pêche est une activité humaine ayant un impact considérable sur l'environnement. Une mauvaise gouvernance, des mécanismes d'application faibles ou inexistants et des subventions excessives et non réglementées ont entraîné la surexploitation des stocks de poissons dans le monde entier, en produisant des conséquences potentiellement désastreuses sur l'écosystème marin et la sécurité alimentaire. Cependant, les pratiques de pêche non durables sont également liées à des abus à bord des navires de pêche : les organisations internationales et non gouvernementales attirent progressivement l'attention sur les pratiques répandues de violations des droits de l'homme et de crimes en mer, en appelant à repenser le régime international pour la conservation et la gestion des pêches en vue de concilier la sécurité économique et environnementale avec la dimension sociale de la pêche durable.Dans ce contexte, la présente thèse de doctorat aborde les problèmes conceptuels et pratiques qui se rattachent à la protection des individus impliqués dans ou autrement affectés par l'activité de pêche, en se concentrant particulièrement sur les victimes à bord des navires de pêche. La thèse s'appuie sur les études relatives à l'interaction des régimes en vue de favoriser le dialogue entre le droit international des droits de l'homme et le droit de la mer, deux régimes relevant du système plus large du droit international public. Après avoir exploré la portée de la question de recherche et fourni le contexte théorique et factuel, le premier chapitre se penche sur le régime du droit des droits de l'homme et examine la notion de juridiction telle qu'elle s'applique aux violations des droits de l'homme en mer, en étudiant en particulier l'utilisation potentielle de la norme sur la juridiction de l'État du pavillon comme critère pour attirer une violation des droits de l'homme à bord de navires de pêche relevant de la juridiction de l'État du pavillon. Le chapitre explore également le contenu et la portée des obligations en matière de droits de l'homme, en se concentrant notamment sur un ensemble de six droits prétendument violés à bord des navires de pêche, à savoir le droit à la vie, l'interdiction de la torture et des traitements inhumains et dégradants, l'interdiction de l'esclavage et des formes modernes d'esclavage, l'interdiction de la privation arbitraire de liberté, le droit à un travail décent et le droit à la santé. Ensuite, le deuxième chapitre se concentre sur le droit de la mer, en retraçant spécifiquement le développement historique qui a conduit à la consolidation du régime actuel de la pêche et en explorant la portée de la notion de pêche illégale, non déclarée et non réglementée et du phénomène de la criminalité dans le domaine de la pêche. Enfin, le dernier chapitre traite de la notion de juridiction telle qu'elle est utilisée dans le droit de la mer, en étudiant spécifiquement son contenu en ce qui concerne tous les acteurs étatiques de ce régime, à savoir l'État côtier, l'État du pavillon, l'État du port et l'État du marché. En particulier, ce chapitre examine de plus près les obligations de chaque État en ce qui concerne la protection de la personne à bord des navires de pêche, en accordant une attention particulière aux pouvoirs d'exécution de l'État côtier et à l'exercice par l'État du pavillon du contrôle des ses navires. Enfin, et surtout, il apporte un éclairage sur la contribution potentielle que les États du port et les États du marché pourraient apporter à la protection des personnes à bord des navires de pêche.
Keywords: Droit de la mer; Droits de l'homme; Fisheries regime; Fisheries resources; Fishing vessels; Human Rights; Law of the Sea; Navires de pêche; Pêches; Ressources halieutiques; Régime de pêche

Confidentiality in International Commercial Arbitration: Is it an Accepted Principle, and if so, Should the Model Law Regulate it? - Kenny, Caroline Majella (Monash University, 2023)
This thesis examines two research questions: first, whether confidentiality in international commercial arbitration (‘ICA’) is an ‘accepted principle’, and second, if the answer to the first question is positive, whether confidentiality should be regulated by the United Nations Commission on International Trade Law (‘UNCITRAL’) Model Law on International Commercial Arbitration (1985), with amendments adopted in 2006 (‘Model Law’) and how such a provision would be framed. To place the questions in context, there is empirical evidence that confidentiality is expected by users of ICA but despite this expectation there appears to be no uniform approach on confidentiality in national laws and institutional rules.
Keywords: Arbitrage; Arbitragem; Arbitration; Confidentiality; UNCITRAL Arbitration Rules; UNCITRAL Model Law

Liability in the atmosphere of groups of companies - Motassim, Sofia (Universitat de Barcelona, 2023)
Groups of companies are a complex corporate structure, whose regulation can be problematic, especially when it comes to liability. Indeed, liability within corporate groups draws forth a series of issues principally due to the principles of separate corporate personality and limited liability. In the context of limited liability, which is based on the notion of separate legal personality, the main issue waxes the protection of the creditors, in particular the creditors of the subsidiaries. One can find three regulatory templates for handling corporate groups and their liability: policing via general company and/or civil law (such as the English model); policing via special group legislation (such as the German model); and policing via branches of law such as insolvency law, antitrust law, and contract law, among others (which is the case in numerous jurisdictions, either coupled with the first or the second model). Lifting the corporate veil has come as an answer to corporate separateness, by permitting to ignore the shareholders’ limited liability and hold them personally liable for the debts of their companies in specific circumstances. However, one can hardly find cases in which the corporate veil has been successfully lifted, due to many factors. Other important questions that are posed in the scope of corporate groups liability are the parent company’s liability for the payment of its daughter companies’ debts when insolvency strikes and other respects, besides the matter of group liability. Furthermore, liability is as well a key player in terms of tort law, and corporate social responsibility has therefore found a place in the sun in the present climate.
Keywords: Ciències Jurídiques; Commercial law; Conglomerate corporations; Corporations; Derecho mercantil; Dret mercantil; Econòmiques i Socials; Grupos de empresas; Grups d'empreses; Liability (Law); Responsabilidad (Derecho); Responsabilitat (Dret); Sociedades; Societats

Developing a regulatory framework for electronic commerce in the Southern African Development Community: the prospects and challenges - Chimeri, Vongai (University of Fort Hare; Faculty of Law, 2023)
Keywords: Community law; E-commerce; Electronic Commerce; Electronic Transactions; Intra-regional trade; Regional integration; SADC; SADC Model Law

The interface between competition and intellectual property law : finding common ground and resolving the tensions between these areas of law from a South African perspective - Dercksen, Juletha-Marie (Stellenbosch University, 2023)
Competition law and intellectual property law share the objective of incentivising innovation. However, this objective is achieved in different ways, which, at times, can create tension between the two areas of law. It is imperative that this tension at the interface of competition law and intellectual property law is resolved in a manner that encourages innovation. Issues regarding the licensing of intellectual property, Standard Essential Patents, pay-for-delay agreements and no-challenge clauses are instances where the tension between competition law and intellectual property law is especially prevalent. These instances will be discussed in detail, and what is learnt from how the European Union and Australia handles it, will be applied to South Africa. The European Union, Australia and South Africa have different ways of dealing with situations where the exercise of intellectual property rights has an effect on competition. The European Union has block exemptions, which contains “safe havens” for conduct in specific circumstances. The block exemptions are often accompanied by guidelines, providing firms and individuals with greater detail in order to self-assess their compliance with the exemption. Australia has authorisation, notification and class exemption procedures. Firms can apply to the Australian Competition and Consumer Commission to authorise conduct that might potentially breach the Competition and Consumer Act 2010. Exemptions may also be granted more broadly by the Australian Competition and Consumer Commission in terms of the class exemption procedures. In South Africa, the law concerning the interface between competition law and intellectual property is still in its infancy, and a lot can be learned from jurisdictions like the European Union and Australia regarding the most efficient way to handle this tension. Currently, the Competition Act 89 of 1998 in South Africa contains Section 10(4), the intellectual property exemption clause. A firm can apply to the Competition Commission for an intellectual property exemption from the application of Chapter 2 of the Competition Act “to an agreement or practice, or a category of agreements or practices” which pertains to the exercise of intellectual property rights. However, it is submitted that Section 10(4), by itself, is not the most efficient mechanism to resolve the tension that arises at the interface of competition law and intellectual property law in a way that incentivises innovation. It is proposed that the exemption provision can be made more effective if it is properly applied in conjunction with class exemptions and guidelines.
Keywords: Antitrust law; Australia; Competencia; Competition Act, 1998; Competition law; Conflict of laws; Intellectual property; South Africa; Trade regulation

The legal regulation of trade union recognition in South Africa in historical and comparative context - Germishuys-Burchell, Wilhelmina (Stellenbosch University, 2023)
This study investigates the impact and importance of the legal regulation of trade union recognition and associated challenges in South Africa. It evaluates the current regulation of trade union recognition, including legislation and judicial attitudes apparent from the interpretation, application, and enforcement of such legislation, to ascertain its continued appropriateness in the current South African industrial relations environment. The study considers the policy choices of both voluntarism and majoritarianism underlying the Labour Relations Act 66 of 1995 (“LRA”) and the “workplace” constituency to which it applies as factors that might be contributing to challenges experienced in the current regulation of collective bargaining in South Africa. It evaluates the current model of trade union recognition and representativeness as it applies to the acquisition by trade unions of organisational rights, collective bargaining rights and trade union recognition for purposes of retrenchment consultation. It recognises that the specific model chosen to regulate the representative status of trade unions has a significant effect on the ability of trade unions to organise and conclude collective agreements and, as such, on the distributive effects of such agreements in the labour market and broader society. The study commences with an historical overview of the regulation of trade union recognition under the 1956 LRA and thereafter considers the 1995 LRA as a product of criticism against the 1956 LRA. Specific issues considered, largely based on the analysis of the relevant decisions by the Constitutional Court, include the following: the impact of Constitutional Court jurisprudence relating to trade union recognition on the process of collective bargaining and on the legal regulation of the right to strike; the role of representativeness and its link with the workplace as the constituency for recognition and acquisition of organisational rights; the often winner-takes-all effect of the current model on collective bargaining as a major cause of labour unrest; the reactive role the legislature has played over the past, almost three decades to address challenges; the extent to which intervention should take place to safeguard the institution of collective bargaining from being undermined as well as the regulation of collective agreements as the product of collective bargaining and as the primary source of terms and conditions of employment. The comparative review of Canadian law focuses on a number of issues selected specifically for their potential to provide insights into how the weaknesses in South African regulation may be remedied. This includes insights into the accommodation of special or significant minority interests and how to address recognition in the context of multi-location employers. The thesis concludes with remarks on the insights gained from the Canadian model and the 1956 LRA. Where appropriate, suggestions are made on the way forward for South Africa as to the appropriate regulation of trade union recognition and representativeness.
Keywords: Collective bargaining; Collective labor agreements; Dismissal of employees; Employee rights; Industrial laws and legislation; Labor disputes; Labor unions; South Africa

Mandatory Environmental, Social and Governance (ESG) Regulations: ESG Performance, Corporate Finance, and Investment - Michael, Emmanuel (Victoria University of Wellington, 2023)
This thesis investigates the relationship between cross-country mandatory environmental, social and governance (ESG) regulations and firm-level outcomes, such as ESG performance, corporate finance, and investment, for both developing and developed countries. ESG performance is initially examined to determine whether mandatory ESG regulations affect it and to what extent. Second, the study investigates the impact of mandatory ESG on corporate finance and investment. Lastly, the study explores whether mandatory ESG regulations affect firm-level outcomes based on countries' governance and economic systems, and industries. The study uses a large sample of 69,010 firm-years across 73 countries, over the period 2005 – 2020 to address the foregoing issues. In addressing the impact of mandatory ESG regulations on ESG performance, the study employs a difference-in-differences (DiD) design. The DiD technique can isolate the effect of regulatory shocks to firm-level outcomes. According to the DiD analysis conducted, cross-country mandatory ESG improves firm-level ESG performance in developed countries, but not in developing countries. The study also concludes that mandatory ESG regulations have a positive impact only on ESG components in developed countries and have a more dominant impact on environmental (E) component. The findings are robust to a range of checks and test cases, including a triple DiD design set-up and propensity score-matched sample. The study employs an investment Euler equation framework and generalised method of moments (GMM) estimators to explore how mandatory ESG impacts corporate finance and investment. Euler frameworks account for the dynamic nature of investment, whereas GMMs account for endogenous dynamics in dynamic models. The study demonstrates that mandatory ESG increases corporate investment by increasing firms' access to external funds. The findings are robust to a battery of tests, including a triple DiD design set-up, propensity score-matched sample and the parallel trends assumption. Using an investment Euler equation framework and the GMM estimators, the study explores whether the impact of mandatory ESG on corporate finance and investment is dependent on a country's governance and economic system. When mandatory ESG is affected by country factors such as governance systems and economic well-being, the effect of mandatory ESG on investment via internal finance channel persists, according to the study. However, while consistent results are found in developed countries, inconsistent results are found in developing countries. According to the study, oil, gas, and mining firms are likely to respond effectively to mandatory ESG regulations because of increased scrutiny and pressure. Overall, the findings from the study imply that cross-country mandatory ESG has had a positive impact on corporate ESG performance, finance, and investment. For firms located in developed countries, these findings hold consistently, while for those located in developing countries, the opposite holds true. Also, the study reveals that firms in the oil, gas, and mining industries effectively respond to regulatory requirements. As a result, this study provides policy makers and accountants with an understanding of how mandatory ESG impacts firm ESG activities and performance, which is crucial for regulatory reforms.
Keywords: Corporate Finance; Cross-Sectional Analysis; Developed countries; Developing countries; Economic Models and Forecasting; Finance; Financial Economics; Investment; Investment Euler equation; Mandatory ESG disclosure regulations; Panel Data Analysis; Sustainability Accounting and Reporting; Time-Series Analysis

The Double Life of State-Owned Enterprises in International Economic Law: States, Corporations or Both? - Kikarea, Eirini (University of Cambridge, 2023)
State-owned enterprises (SOEs) have recently gained prominence in global markets and feature among the world’s most influential enterprises. The aim of this research project is to analyse the international norms in force regulating whether SOEs are considered state or non- state actors, and their conduct state or non-state conduct, the interpretation and application of these norms by adjudicators in different international regimes, and to provide alternative prisms through which these rules and decisions can be assessed and re-thought by political actors. I show that, in relation to SOEs, the concepts ‘state and ‘act of state’ have been ascribed diverse meanings by adjudicators and other international actors, who have employed legal standards with divergent wording and thresholds when dealing with similar questions. I argue that the fragmented meaning of these terms should be understood, in part, as a result of the inherent malleability of these terms and the different expert vocabularies employed across regimes. It is exhibited that adjudicators in the international trade and investment regimes are more inclined towards piercing the corporate veil of SOEs, potentially evidencing the existence of biases against SOEs, which are perceived as inherently economically inefficient and politically motivated actors in an indiscriminatory manner. In the last chapter, I introduce alternative lines of thought regarding the regulation of SOEs in international law. I suggest that, instead of engaging in theoretical discussions on the proper delineation between the public and the private sector, it is more useful to focus on the distributional impact of international rules on various actors, especially on developing and emerging economies where the presence of SOEs is very high. Such alternative prisms of analysis open paths for future research and practice, with the goal of designing an international economic order that incentivises institutional experimentation in the pursuit of economic development and distributional equity.
Keywords: International Economic Law; International Investment Law; International law; International trade law; Public enterprises; State capitalism; State-owned enterprises

The adoption of international financial reporting standards and foreign direct investment inflows: the moderating effect of the institutional environment in Africa - Simbi, Chipo (Rhodes University; Faculty of Commerce, Accounting, 2023)
Globalisation has created a need for an international accounting language to facilitate the smooth flow of trade across countries. In 2003, in an effort to establish a global financial reporting language, the International Accounting Standards Board (IASB) developed a single set of high-quality accounting principles known as the International Financial Reporting Standards (IFRS). Over the last decade, several African countries have adopted IFRS, and Africa has become the second-largest adopting continent after Europe. IFRS promotes improved quality of disclosure of accounting transactions, reduces information asymmetry between preparers and users of financial information, lowers the cost of investing, and breaks down information barriers to cross-border investment. Researchers suggest many benefits of IFRS adoption for macroeconomic indicators such as Foreign Direct Investment (FDI). The reduction in information acquisition and processing costs which translates into the reduction in investment costs, has been cited by most researchers. Researchers have argued, however, that the economic benefits of IFRS in Africa depend on the strength of the institutional environment. They also argue that the Western environment in which the IFRS was developed differs from the African environment. Thus, the universal approach of the IASB may not be appropriate due to the historical, social, economic and political context of African countries. The impact of the adoption of IFRS by African countries requires further examination, particularly as a weak institutional environment confronts many African countries. Three research questions are designed for this study; (1) Is there a significant change in FDI inflows for IFRS adopters in selected African countries after the adoption? (2) Is there a significant change in FDI inflows due to the institutional environment? (3) Does the institutional environment in IFRS-adopting countries moderate the effect of IFRS on FDI in selected African countries? The present study is underpinned by the new institutional theory, the information asymmetry theory, the eclectic theory and the signalling theory, each of which provide reasons why African countries have adopted IFRS. Nine hypotheses are developed, based on the research questions, and tested using the Systems General Method of Moments and the Difference-in-Difference method. The study uses data from 26 African countries, 15 adopting and 11 non-adopting countries, over the period 1996 - 2018. First, the study establishes that the adoption of IFRS positively and significantly affects FDI inflows into the selected sample of African countries. Second, the study concludes that legal enforcement, accounting and auditing standards enforcement, and language origin positively and significantly impact FDI inflows into these countries. Legal origin, however, has a positive but insignificant association with FDI inflows. Third, legal enforcement, historical ties, accounting and auditing enforcement and the quality of the institutional environment are found to moderate the effect of IFRS adoption on FDI inflows. These results indicate that IFRS is a crucial determinant of FDI inflows into African countries, but a supportive institutional environment is needed for African countries to attract FDI inflows after adoption. The results contribute to the accounting and finance literature on FDI into African countries, and may assist the investment community to assess the institutional risk associated with investing in IFRS adopting African countries.
Keywords: Accounting; Auditing; Difference in differences; FDI; Foreign direct investment; Generalized method of moments; IFRS adoption; Institutional infrastructure; International Financial Reporting Standards; Investments

Legal harmonisation of non-tariff barriers of regional economic communities as a catalyst to the realisation of the African continental free trade area - Achancho Etagha Epse Abia, Elisabeth (University of KwaZulu-Natal, 2023)
Legal harmonisation is an integral aspect of regional integration and the desire to promote regional and sub-regional economic integration in Africa is exemplified by the establishment of the African Continental Free Trade Area (AfCFTA) in 2018. The 2012 decision of the AU to create the CFTA by 2017 was reiterated in Aspiration two of Agenda 2063. The legal harmonisation of non-tariff barriers has been a vital instrument in the achievement of EU economic integration and the Organisation for the Harmonisation of Business Laws in Africa (OHADA). The study seeks to critically examine the theoretical and conceptual underpinnings of regional integration and legal harmonisation of non-tariff barriers by the AU and RECs. It also analyses the current political, economic, and legal reinforcements to regionalism in Africa and practices needed to advance intra-regional trade within the framework of Agenda 2063. This was done by evaluating the key legal frameworks of the AU (the Abuja Treaty, the Constitutive Act of AU, 2007 Protocol on relations between AU and RECs and Agenda 2063) with the aim of identifying best practices, gaps and impediments pertinent to strengthening Agenda 2063 CFTA. At the end of the study, the abilities of three selected RECs (SADC, COMESA and EAC) were assessed to drive home the AfCFTA. This was done by identifying flaws in existing treaties of RECs, while advancing a model of legal harmonisation of NTBs between them. It was found out that the AU and RECs have not vigorously considered the significance of legal harmonisation in their integration agendas. This resulted in the lack of unambiguous and concrete provisions for the legal harmonisation of NTBs in their guiding policies. Where some attempts are evident, such as in the EAC, they have been implemented unsatisfactorily with lack of a compliance mechanism. This study contended that if legal barriers to free trade are not eliminated, even if all other barriers were to be removed, the effective realisation of the AfCFTA would still be hindered. Hence, this study recommends the principles of direct applicability and direct effects of regional laws to addressing the legal harmonisation challenge underscored. Iqoqa Ukuvumelanisa okusemthethweni kwezithiyo ezingakhokhiswa intela kuyisici esibalulekile sokudidiyelwa kwesifunda kanye nesifiso sokugqugquzela ukuhlanganiswa komnotho wesifunda kanye nesifunda esincane e-Afrikha sibonakala ngokusungulwa kweNdawo Yezwekazi Lase-Afrikha Yokuhweba Ngokukhululekile (i-AfCFTA) ngowezi-2018. Isinqumo sowezi-2012 se-AU sokwakha i-CFTA ngowezi-2017 saphindwa Esifisweni Sesibili soHlelo- 2063. I-CFTA iphinde ibe wuhlelo olubalulekile oHlelweni-2063 futhi impumelelo yayo ibalulekile. Ucwaningo luhlose ukuhlola ngokujulile izisekelo zethiyori nezomqondo zokuhlanganiswa kwesifunda kanye nokuvunyelaniswa kwezomthetho kwezithiyo ezingakhokhisi yi-AU kanye nama-REC. Iphinde ihlaziye ukuqiniswa kwamanje kwezepolitiki, ezomnotho, kanye nezomthetho kuzwelonke e-Afrikha kanye nezinqubo ezidingekayo ukuze kuthuthukiswe ukuhwebelana kwangaphakathi kwesifunda ngaphakathi kohlaka loHlelo-2063. Lokhu kwenziwa ngokuhlola izinhlaka zomthetho ezibalulekile ze-AU (iSivumelwano sase-Abuja, UMthetho-sisekelo we-AU, 2007 Protocol on relationship between AU and RECs and Agenda 2063) ngenhloso yokuhlonza izindlela ezingcono kakhulu, amagebe kanye nezithiyo ezihambisana nokuqinisa uHlelo-2063 CFTA. Ekupheleni kocwaningo, amakhono ama-REC amathathu akhethiwe (i-SADC, i-COMESA kanye ne-EAC) ahlolwa ukuze aqhubekisele phambili i-AfCFTA. Lokhu kwenziwa ngokuhlonza amaphutha ezivumelwaneni ezikhona zama-RECs, ngenkathi kuthuthukiswa imodeli yokuvumelana okusemthethweni kwama-NTB phakathi kwawo. Kwatholakala ukuthi osopolitiki base-Afrikha abazange bayicabange indlela eqinile yokuhlanganisa umnotho wesifunda, nakuba indlela enjalo yaphakanyiswa abasunguli besifunda sase-Afrikha. I-AU kanye nama-REC awazange acabangele ngamandla ukubaluleka kokuvumelana kwezomthetho ezinhlelweni zawo zokuhlanganisa. Lokhu kuholele ekuntulekeni kwezinhlinzeko ezicacile nezibambekayo zokuvumelana ngokusemthethweni kwama-NTB kuzinqubomgomo eziqondisayo. Lolu cwaningo lwagomela ngokuthi uma izithiyo ezingokomthetho zokuhwebelana ngokukhululeka zingaqedwa, ngisho noma zonke ezinye izithiyo zizosuswa, ukufezeka ngempumelelo kwe-AfCFTA kusazothikamezwa. Ngaphakathi kwalokhu kwangemuva, lolu cwaningo luncoma izimiso zokusebenziseka okuqondile kanye nemiphumela eqondile yemithetho yesifunda ukuze kubhekwane nenselele yokuvumelana kwezomthetho egcizelelwe.
Keywords: Common External Tariff; Direct Effect; Legal harmonisation

Environmental protection under national legislation and agreements between oil and gas multinational corporations and host communities - Adedipe, F. (Canterbury Christ Church University, 2023)
The exploration, production and shipment of crude oil and gas by multinational corporations (MNCs), involved in bilateral treaties in Nigeria has perpetrated environmental disasters upon host communities. This has been as a result of oil and gas leaks from MNCs facility into the air, land, water, marine habitat, and cultural life of host communities are heavily polluted. International law has attempted to regulate the activities of MNCs particularly in the protection of the environment in which they operate through four main treaties: Universal Declaration of Human Rights,1International Covenant on Economic, Social and Cultural Rights (ICESCR), 2 Declaration of the United Nations Conference on the Human Environment (Stockholm Declaration)3and Declaration of the United Nations on Environment and Development (Rio Declaration). In addition, the demand for environmental protection is foregrounded under the right to life recognized in article 6 of the International Covenant on Civil and Political Rights (ICCPR). However, a major criticism of international law is its inapplicability to non-State actors such as corporations. This creates a lacuna in the legal framework of protections which has been exploited by opportunistic MNC’s. International soft law such as the Global Compact, Organization of Economic Cooperation and Development (OECD) Guidelines for Multinational Enterprises and United Nations Guiding Principles (UNGPs) on Business and Human Rights encourages corporations to respect environmental rights and creates substantive standards for States to hold corporations accountable for environmental and human rights violations. The challenge remains that these international laws having soft law status are not binding on corporations. Also, a further problem is that several developing state governments may be complicit in the environmental abuses perpetrated by MNCs for the purpose of boosting economic development. Therefore, this research proposes the regulation of MNCs under national legislation and bilateral investment treaties. It recommends certain preventive and mitigation measures against the adverse environmental effect of their activities in the exploration of natural resources, waste disposal and other connected operations in developing communities in Nigeria. Some of these preventive measures include environmental impact assessment (EIA), mandatory reporting and disclosures, community stakeholder participation, environmental management and safety practices, with activity, temporal and spatial management as mitigation measures. Also, clean-up and compensation by MNCs are effective remedies for environmental abuses. Furthermore, fines, blacklisting, withdrawal of license and criminal charges are recommended for the enforcement of environmental protection of host communities.
Keywords: Agreement; Environment (protection); Host communities; Multinational corporations; Oil and Gas Industry

The regulation of Corporate phoenix activity in South Africa - Basson, André Stephan (University of Johannesburg, 2023)
Phoenix activity involves conduct whereby a failing company (the old company) is replaced by a second company (the new company) in the operation of the same or a similar business and that involves the same or similar company controllers. Transactions of this nature can be legal and even be beneficial to society, since entrepreneurs who pursue a viable business may, if the new company succeeds, benefit the economy and many other stakeholders. These transactions are referred to as legal phoenix activity. Problems arise however when phoenix activity is engaged in with the goal of evading the debt of the old company, known as illegal phoenix activity. In other cases, even well-intentioned company controllers can cause significant harm by resurrecting a fundamentally flawed business. This conduct, although not illegal, is unduly prejudicial to stakeholders and is known as problematic phoenix activity. While this thesis focuses on illegal phoenix activity, several measures identified should also curb problematic phoenix activity. This study identifies the elements and common characteristics of illegal phoenix activity. It then analyses regulation pertaining to those elements and common characteristics with the aim of finding effective solutions to the problem. This includes evaluating measures that reverse prejudicial transactions that occur during illegal phoenix activity as well as holding complicit parties, such as company controllers and the new company, accountable for their actions. Regulation aimed at preventing and investigating illegal phoenix activity is also considered. This thesis uses the comparative legal approach to analyse regulatory responses to illegal phoenix activity. Australia, the United Kingdom, and the United States of America are examined. Several reported cases in South Africa involving what appear to be illegal phoenix activity are explored, along with the existing measures that are applicable to illegal phoenix activity in South Africa. A single anti-phoenix provision is undesirable as it has the potential to unjustifiably infringe on legal phoenix activity. This thesis proposes a multi-pronged approach, which involves a combination of better enforcement of existing laws and the introduction of smaller targeted amendments to legislation aimed at reducing the incidence illegal phoenix activity.
Keywords: ABUSE OF THE CORPORATE FORM; Bankruptcy fraud; Evasion of liability; Fraud on creditors; Phoenix activity; Phoenixism; Strategic bankruptcy; Successor liability; Transactions prejudicing creditors; Transfers at an undervalue

A legal analysis on how France, Germany, the European Union and South Africa responded to the United Nations guiding principles on business and human rights - Buis, Jeanette (University of Pretoria, 2023)
Globally, companies pursue profitability; they want lower prices for the goods they buy and for the services they use. To gain profit and keep their prices low, they contribute to human rights violations and/or the devastation of the environment. The UNGP is the UN unanimously endorsed instrument that encourages states to pass legislation to compel companies to exercise human rights due diligence and to report on their efforts. The United Nations Guiding Principles (UNGP) impose a duty on companies to conduct human rights due diligence that apprises them of possible human rights or environmental risk exposure in their international operations. States have a responsibility to assist those harmed by a company’s activities to seek judicial relief. The UNGP is a soft law instrument but has had a major effect in the field of business and human rights. Though a voluntary obligation, the UNGP has become the reference document and is used by Civil Society Organisations (CSO) to pressure states into passing regulations on business and human rights. In 2016 Germany passed a National Action Plan (NAP) and the Lieferkettensorgfaltspflichtgesetz (Supply Chain Due Diligence Act) in 2021. France passed a Vigilance Law (Loi de Vigilance) in 2017. Additionally, a UN resolution has initiated a treaty-making process, which might lead to an internationally legally binding instrument that will articulate companies’ responsibilities to avoid, mitigate and remedy human rights violations that their activities cause. The South African government’s response to the UNGP has focused on negotiating a legally binding instrument at an intergovernmental level. This research examines three countries’ varying responses to the UNGP, a soft law instrument. In February 2022 the EU Commission published a proposed directive on corporate sustainability due diligence. The proposed EU legislation aims to advance respect for human rights and environmental protection. The goal is to create a level playing field within the European Union which leads to the exploration of the role China plays in a globalised world. China aims to be more than the world's factory and to become a leader in innovation and high-end manufacturing.
Keywords: CSR; Corporate Social Responsibility; Corporate governance; Human rights due diligence; Mandatory corporate due diligence; RSE; United Nations Guiding Principles; responsabilité sociale des entreprises

The commercial sexual exploitation of children perpetrated by the private sector: can international law be improved? - Hecht, Mark (Université de Sherbrooke, 2023)
International law is a robust system designed to unite world governments in an effort to, inter alia, cease human rights violations and hold those who commit them accountable. As it currently stands, and by its own design, the international human rights legal regime focuses on and applies only to state actors, meaning that violations committed by non-state actors, such as multinational corporations (MNCs), are seemingly conducted with impunity inside this space. Multinational corporations are powerful international players that have undoubtably fostered a significant role in reducing global barriers. By their very nature, they are far more mobile than states, allowing them to evade domestic power and regulatory schemes by detaching from their home state and relocating to a host state with weaker oversight and/or enforcement powers. Simply stated: even though MNCs have better financing, heightened mobility, and a disproportionate amount of influence when compared to world states, they operate with less global accountability. Commercial sexual exploitation of children (CSEC) is a fundamental violation of children’s rights. It consists of sexual abuse by the adult and remuneration in cash or kind to the child or a third person or persons. The child is treated as a sexual object and as a commercial object. Multinational corporations have been implicated in CSEC through acts of omission and commission. And despite the fact that much international law has been drafted to protect children around the world from CSEC—most notably the United Nations Convention on the Rights of the Child and its Optional Protocols—the numbers of children who have been emotionally and physically harmed by and through MNC conduct has only increased in the past decade. There have been numerous efforts by international organizations to address the challenges when regulating and monitoring human rights violations by MNCs. States, civil society organizations, and the private sector itself have also attempted to address these human rights violations through domestic law, modifying international law principles, and with civil regulation. Obstacles exist in the effectiveness of each of these approaches, leaving children at risk with no single effective strategy to combat and address rights violations by MNCs. The dissertation conducts a review of the current landscape of child law, through the lens of corporate accountability for CSEC. Then, it suggests a new alternative, putting forward an international solution to an international problem.
Keywords: Commercial sexual exploitation of children; Convention on the rights of the child; Corporate Social Responsibility; International child law

Land Reform in Sub-Saharan Africa: Exploring Interested Parties Perspectives on Cameroon's Land Tenure and Land Law Reform. - Kenfack Kenjio, Jacques Wilfried (Antioch University, 2023)
This research study seeks to understand interested parties’ perspectives on Cameroon's existing land tenure systems, the 1974 land law, and ongoing efforts to reform this land law. It identifies both concerns and specific recommendations from these parties on the formulation and implementation of future reforms. In the decades following the achievement of independence from European colonizers, most governments in sub-Saharan Africa (SSA) have adopted new national land tenure policies to meet their countries’ needs and aspirations. In some parts of SSA, however, this process of land tenure formalization has negatively impacted the land rights of people observing customary land tenure. This has been a result of government interventions such as compulsory land acquisitions, which while technically legal, are ethically questionable. In the face of this challenge, efforts to reform post-colonial land laws have become a matter of urgency. A national land reform process for Cameroon, announced in 2011 has adopted a multistakeholder approach. My study seeks to understand interested parties’ perspectives on Cameroon’s existing land tenure systems, the 1974 land law, and ongoing efforts to reform the land law. This study applied a case study methodological approach and a convergent mixed-method design. Evidence from this study shows that interested parties in Cameroon are in agreement on 1) the reform of the 1974 land law, 2) the recognition of customary land tenure, 3) the continued use of multistakeholder participation in land law reform, and 4) the promulgation of the new land law through mass sensitization and information dissemination.
Keywords: Government-Driven Land Dispossessions; Land Expropriations; Land Law; Land Reform; Land Tenure; Mixed Methods; Multistakeholder Participation; Sub-Saharan Africa

The Autonomy Doctrine in the Law of Letters of Credit and Demand Guarantees in Libya, Egypt and England: A Comparative Study - Mukhtar Elhouderi, Tajeldin Eissa Saleh (University of Leicester, 2023)
Letters of credit and demand guarantees play a prominent role in financing international trade. They provide assurance of payment and security for the performance of contractual obligations and have been described as the ‘lifeblood’ of international commerce. Autonomy is the central principle for the instruments of letters of credit and demand guarantees. Under the autonomy principle, the bank’s undertaking to pay for the beneficiary ought to be independent of the diversity of other relationships arising from the underlying contract. In spite of the autonomous nature of these instruments, in certain cases, the national laws will recognise some exceptions or limitations that restrict the application of the doctrine of autonomy. Exceptions such as fraud, nullity, and illegality will allow the national courts to interfere and override the autonomy doctrine by considering other matters, even those concerning the underlying contract. Furthermore, the exceptions of unconscionability or abuse of rights have an effective role in providing deep solutions, especially with regard to the problem of abusive calls for demand guarantees. The autonomy principle is recognised under Libyan commercial law but has yet to form the subject of serious academic literature covering its legal aspects. This study, in part, aims to fill that gap and will examine the extent to which legal aspects govern the principle of autonomy and its exceptions under Libyan law with reference to the new Libyan Commercial Code. A comparison of the laws in England, Libya, and Egypt will be conducted to examine how legal matters concerning autonomy and its restrictions in their laws are addressed. Furthermore, consideration will be given to the experience of Singapore, particularly with regard to the unconscionability and nullity exceptions. The results of this study will consider many different exceptions to autonomy and suggest that fraud is not the only exception to autonomy and that it is not imperative that all exceptions in letters of credit be equally applied to demand guarantees.
Keywords: Commerce international; Comparative study; Contractual obligations; Egypt; England; International Trade; International commerce; Letter of credit; Letter of guarantee; Lettre de crédit; Lettre de garantie; Libya; Obligation contractuelle

The goals of competition law for merger analysis in developing jurisdictions : a critical appraisal of merger analysis under Kenyan competition law - Njako, Priscilla Mumbua (University of Pretoria, 2023)
This thesis considers whether jurisdictional exigencies should influence competition law enforcement, with a specific focus on merger analysis. It examines various approaches and schools of thought regarding the goals of competition law and how these play out within jurisdictional parameters. The history of enforcement of American antitrust is scrutinised to establish the nature of the interplay between greater economic policy direction and the goals of competition law. The study also explores the issue of convergence and whether developing jurisdictions should align their competition law to that of developed jurisdictions with mature competition law.
Keywords: American antitrust; Competencia; Competition law; Concurrence (droit); Kenya; Merger analysis

Harmonisation in the rules governing the recognition of foreign judicial ship sales - Shao, Yingfeng (World Maritime University, 2023)
Ships, the high-value asset used in both seagoing and inland navigation, and in which various legal and natural persons have interests, must be secured against legal risks arising from any cross-border legal divergence. Legal certainty of ownership of the ship is therefore desirable but it is under challenge with regard to the judicial sale of a ship: the effects of a judicial sale may be denied in a jurisdiction other than the place where it was sold under the principles of state jurisdiction. Multiple efforts have been made to address legal uncertainty. Particularly important is a new treaty governing the international effects of judicial sales: the United Nations Convention on the International Effects of Judicial Sales of Ships (Beijing Convention). This dissertation is intended to contribute to that process by setting out two tasks; first, it seeks to identify the obstacles to the recognition of foreign judicial sales, providing additional knowledge which may aid national legal orders when deciding recognition approaches; second, it looks for a universal solution that better guarantees recognition which would benefit shipping. A comparative legal research exercise exploring similarities and dissimilarities in the municipal and international laws governing the recognition and sale procedures is undertaken. Research results are presented in this kappa and research papers, exhibiting the profuse difficulties a party seeking recognition may encounter in the current legal framework, and explains the new recognition approach under the Beijing Convention. Based on the research findings, a universal solution is proposed that avoids révision au fond, defines the finality of a judicial sale, and sets forth a fixed number of grounds for denial of recognition which may bring greater certainty. This purported optimal solution should guarantee equal treatment for all foreign sales seeking recognition before the registry while minimising the registrar’s burden of finding and examining foreign laws. In the interest of universality, this solution better accommodates disagreeing principles underlying certain aspects of the sale, viz., the ship’s location at the time of sale, the notification of sale, and the variance in the standard sale, namely, court-approved private sales, in a manner that more states may accept. This solution is largely in line with the recognition approach under the Beijing Convention. Considering the greater legal certainty the new instrument may bring, ratification is supported.

The public domain and the legal protection of Indigenous Knowledge Systems - Verhoef, Gerardus (North-West University, 2023)
IKS stakeholders often debate the divide between indigenous and other knowledge systems. IP rightsholders seek advice on how they can strengthen and secure their proprietary rights or broaden the public domain, while other interest groups such as indigenous peoples and local communities want to know how the public domain can be enclosed. One reason for this divide seems to be that the IP regime operates in a sphere where the public domain is demarcated by individual rights, as opposed to the indigenous knowledge systems regime where the public domain is demarcated by social embeddedness and connected to the land on which indigenous peoples and local communities live. This problem manifested itself over centuries of colonialism and technological development worldwide, but also because indigenous worldviews do not share the pre-appropriation narrative of the public domain than technological advanced societies. Within the context of this narrative the research question was posed, namely "what are the appropriate legal instruments for protecting Indigenous Knowledge Systems without compromising the public domain?" To answer this question, the public domain was analysed from three perspectives, namely international law instruments, human rights and IP rights. It was found that none of these perspectives lead to a narrow interpretation of the public domain – in fact, they all aim to broaden the public domain. These early findings on the public domain assisted to apply the fundamentals of the public domain to international law instruments and their application to IKS. In this regard it has been shown that the existing international law instruments, as well as the natural evolvement of these instruments over time, adequately provides for the protection and commercial exploitation of IKS worldwide. There is a proviso, though: IKS need to be viewed through the WIPO lens, which provides for the distinct delineation of categories of IKS, namely traditional knowledge, traditional cultural expressions and genetic resources. For example, the Bern Convention is founded on the three principles of droits des auteurs, droit moral, and domaine public. The boundaries of the public domain within the context of IKS can be reconciled with all three of these principles, and national legislators merely need to apply these principles to national legislation. With these insights gained on international law instruments, a few countries were analysed to ascertain how they address their local challenges pertaining to IKS. The countries that were analysed all aimed to appreciate international law instruments to which they are signatories, while they develop country specific IKS-related jurisprudence, although it cannot be said to be the same in each country. None of the findings pertaining to these countries could provide convincing arguments as to why a sui generis system for IKS can work. The research then moved to a legal analysis of South African legislation in relation to IKS. It has been shown that in general, South African legislation on IP is well aligned with international law instruments. These findings assisted with the research question at hand and was instrumental with coming to the early conclusion that IKS neatly fits into South Africa's current IP regimes and their associated public domains. Throughout the thesis, the rights and obligations of IKS rightsholders were demarcated since no right is absolute, as has been shown when the South African Constitution was discussed. In this regard, the droit moral of individuals from indigenous peoples and local communities, as well as the indigenous peoples and local communities, are to be respected. This approach led to more practical measures to ensure that matters such as prior informed consent, secrecy and sacredness, equity and access to TK, TCE and GR and benefit sharing were all understood within the boundaries of the public domain.
Keywords: Indigenous knowledge (protection); Intellectual property; Propriedade intelectual; Propriété intellectuelle; Savoirs traditionnels